Examining a "Household" Model of Residential Long-term Care in Nova Scotia - Janice Keefe; Donna Dill; Rachel Ogilvie; Pamela Fancey (McMaster University Library Press, 2017)
In 2006, Nova Scotia began to implement its Continuing Care Strategy which was grounded in a vision of providing client-centered care for continuing care clients, including residents of nursing homes. Considerable evidence pointed to the benefits of the "household" model of care-which led the province to adopt the smaller self-contained household model as a requirement for owners/operators seeking to build government-funded new and replacement nursing homes. The specific goals of the reform (the adoption of the household model) included increasing the proportion of single rooms, improving the home-likeness of the facility, and more generally, providing high-quality care services. The reform was influenced by recognition of the need for change, rapid population aging in the province, and strong political will at a time when fiscal resources were available. To achieve the reform, Nova Scotia Department of Health released two key documents (2007) to guide the design and operation of all new and replacement facilities procured using a request for proposal process: The Long Term Care Program Requirements and the Space and Design Requirements. Results from a research study examining resident quality of life suggest regardless of physical design or staffing approach high resident quality of life can be experienced, while at the same time recognizing that the facilities with "self-contained household" design and expanded care staff roles were uniquely supporting relationships and home-likeness and positively impacting resident quality of life.